Influence of COVID-19 restrictions on patients’ self-reported oral health care needs - Sekundo, Caroline; Langowski, Eva; Frese, Cornelia (Oral health & preventive dentistry, 2021)
Purpose: To assess how current COVID-19 restrictions regarding elective dental procedures influence patients’ self-reported oral health care needs at a University Hospital in Germany. Materials and Methods: Patients with COVID-19 induced cancellation of elective treatment appointments previously scheduled for the period March 16th to April 30th 2020 were contacted by telephone and questioned about the occurrence of oral health problems, pain, self-reported treatment needs, and the use of emergency dental services. Data were analysed retrospectively. Results: Information on 370patients aged between 1 and 91years was included. 16.2% (n=60) of patients reported ﻿hav﻿ing experienced an oral health problem for which they requested timely dental treatment. Within this group, the most frequent complaints were pain or tooth hypersensitivity (42.4%, n=26), insufficient restorations (28.8%, n=17) and gingival or periodontal problems (23.7%, n=14). Associations between the type of treatment pending and the report of an oral health problem were considerable for patients awaiting treatment under full anesthesia, surgical procedures and endodontic treatment (p=0.001; 0.003 and 0.048, respectively). Problems were reported most frequently in these treatment groups, ranging from 27.7% to 100%, compared to 12.6% among patients scheduled for routine check-ups. Overall, 8.6% (n=32) were experiencing pain, of whom 5patients experienced constant pain. However, only 1.9% (n=7) of patients made use of emergency dental services. Conclusions: The results suggest that while the postponement of routine check-ups is justifiable during emergency situations, the long-term cancellation of surgical and endodontic therapies must be viewed critically.